(untitled) (Journal of Global Accounting, 2023)
The main aim of this study is to empirically examine the effect of electronic accounting on the operation of deposit money banks in Nigeria. Specifically the study sought to determine whether e-accounting has restored customers of the safety of their fund and whether channel delivery system can sustain customer patronage. Survey research designs were adopted for the study. Data were collected through survey in which questionnaire was administered on a sample of 180 was purposively collected from population of selected banks. Data collected were analyzed by use of means and standard deviation and the formulated hypotheses were tested by the use of t-test and Analysis of Variance statistical tools. The findings confirm that emergence of e-accounting has restored confidence of the customers on the safety of their funds and delivery channels systems have helped to sustain customer’s patronage in Deposit Money Banks at 5% level of significance. Therefore, the researchers recommend that Central Bank of Nigeria should make it mandatory for all banks to embrace e-accounting.